Application of pervaporation membranes to the direct carboxylation of ethene glycol using CeO2-based catalysts—Comparison of the batch reaction to a flow reaction in SC-CO2. (April 2022) - Linsalata, Domenico; Aresta, Michele; Bortoluzzi, Marco; Ditaranto, Nicoletta; Nocito, Francesco; Dibenedetto, Angela
Abstract: The reaction between ethene glycol-EG and CO2 to afford the cyclic ethene carbonate-EC has been studied in solvent-less conditions and in absence of water traps but using pervaporation membranes to eliminate water. The parameter space of the reaction (temperature, pressure, catalyst loading, time of reaction) has been investigated, filling a gap existing in the scientific literature, and the optimal reaction conditions set as: 408 K, 2 h, 10% w/w cat, 5.0 MPa of CO2 . Under such conditions an equilibrium constant equal to 8.3 × 10 −4 has been calculated based on the equilibrium composition of the reaction mixture that contains 0.33% mol of EC. Such value is higher than that calculated from available thermodynamic data in the scientific literature (3 ×10 −26 ) showing that they need a correction to be adapted to a condensed phase. Using a SC-mixture of EG and CO2 (with a molar ratio CO2 /EG equal to 60), 0.25 ± 0.01% EC is formed in a contact-time of the order of 4–6 min with respect to 120 min in a batch reaction, justified by the higher CO2 /EG molar ratio. Water is formed in excess with respect to the reaction stoichiometry, due to parasite reactions that bear to the formation of di- and tri-ethers and linear carbonate. Such excess water (up to ten times the expected value) strongly influences the equilibrium composition and disfavour the formation of EC. The application of a NaA-type pervaporation membrane can increase the EC-equilibrium concentration of 3–4 times. EG is shown to be less performant than ethanol due to the easier etherification that causes extra-formation of water, that pushes the equilibrium to the left, and to its viscosity that affects the performance of the membrane. The reaction time must be kept under control as a long reaction time favours the formation of ethers, more than EC. A DFT study aimed to explore suitable intermediate species in the catalysed reaction explains that etherification and carbonation are competitive reactions. Graphical Abstract: ga1 Highlights: Parameter space investigation for ethene glycol direct carboxylation in absence of chemical water traps. Effectiveness of coupling the direct carboxylation of ethene glycol with pervaporation membranes for water removal. Reduction of the reaction time in a flow reaction in SC-CO2 with enhanced molar ratio CO2 /EG. Competition of ethers-formation with carboxylation of EG is shown by DFT calculations.